Does rice farming shape individualism and innovation? A response to Talhelm et al. (2014) - Ruan, Jianqing; Xie, Zhuan; Zhang, Xiaobo (International Food Policy Research Institute, 2014)
Talhelm et al. (2014) provided an original rice theory to explain large psychological differences across countries and even within countries and their impact on innovation. However, their findings are subject to the problems of sample bias, measurement error, and model misspecification. After correcting these problems, most findings in the original paper no longer hold. The authors of this paper collected data on collectivism from other sources and linked them with rice areas but failed to find any relationship as predicted by the rice theory. The role of rice farming in shaping cultural psychology and innovations seems to be much more muted.